STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DISEKOLAH MENENGAH PERTAMA - Setiyanti, Wita; Setyowati, Susdaryanti Eko; M, Ngurah Ayu Nyoman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Education has a strategic role in increasing the excellence of a nation. The principal's strategy is an important factor in determining the success of improving quality in schools. This research aims to describe the principal's strategy for planning, implementation, supervision and obstacles in improving the quality of education. The right principal strategy will make a change in the quality of education. This research aims to map the results of previous research related to school principal strategies in improving the quality of education. The method used is literature study. Data collection was carried out by collecting scientific articles relevant to the research topic. The analysis used is content analysis. From the analysis carried out by researchers, the findings in this study are as follows. 1) The school principal's strategy for improving the quality of education consists of teaching staff development strategies, learning strategies, strategies for increasing academic and non-academic achievements, facilities and infrastructure strategies, financing strategies, public relations strategies (public relations), and monitoring and evaluation strategies. 2) Supporting factors for implementing the principal's strategy in improving the quality of education. 3) Factors inhibiting the implementation of school principal strategies in improving the quality of education. 4) The impact of the principal's strategy in improving the quality of education. ABSTRAKPendidikan memiliki peran yang strategis guna meningkatkan keunggulan suatu bangsa. Strategi kepala sekolah merupakan faktor yang penting dalam menentukan keberhasilan peningkatan mutu disekolah. Penelitian ini bertujuan mendesripsikan strategi kepala sekolah dari perencanaan, pelaksanaan, pengawasan dan hambatan dalam meningkatkan mutu Pendidikan. Strategi kepala sekolah yang tepat akan membuat suatu perubahan kualitas pendidikan. Penelitian ini bertujuan untuk memetakan hasil penelitian terdahulu terkait dengan strategi kepala sekolah dalam meningkatkan mutu pendidikan. Metode yang digunakan adalah studi literatur. Pengumpulan data dilakukan dengan mengumpulkan artikel ilmiah yang relevan dengan topik penelitian. Analisis yang digunakan yaitu analisis isi. Berdasarkan analisa peneliti, hasil penelitian ini adalah sebagai berikut. 1) Strategi kepala sekolah dalam meningkatkan mutu pendidikan, terdiri dari strategi pengembangan tenaga pendidik, strategi pembelajaran, strategi peningkatan prestasi akademik dan non akademik, strategi sarana dan prasarana,strategi pembiayaan, strategi hubungan masyarakat (humas), dan strategi pengawasan dan evaluasi. 2) Faktor pendukung implementasi strategi kepala sekolah dalam meningkatkan mutu pendidikan. 3) Kendala implementasi strategi kepala sekolah dalam meningkatkan mutu pendidikan. 4) Dampak strategi kepala sekolah dalam meningkatkan mutu pendidikan.